1985
DOI: 10.1111/j.1476-5381.1985.tb08882.x
|View full text |Cite
|
Sign up to set email alerts
|

The properties of the clonidine withdrawal response of guinea‐pig isolated ileum

Abstract: 1The dependence-inducing effects of clonidine were investigated on the guinea-pig isolated ileum. Clonidine produced relaxation of the ileum with a threshold concentration between 0.01 and 0.1 imol I-'. Washout of clonidine did not induce a withdrawal contraction. 6 Since clonidine dependence may be induced as rapidly as opiate dependence in the ileum and the pharmacology of the withdrawal responses is similar, it is suggested that they both induce the same post-receptor neuronal feedback disturbance in which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
1

Year Published

1989
1989
2009
2009

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 20 publications
3
11
1
Order By: Relevance
“…The washout contracture to adenosine, 5,uM, was abolished in seven preparations (from seven animals) by addition of the SP antagonist, spantide, 1O#UM, 30s before washout of the bath (Figure 1). Thus adenosine produced similar actions on the ileum to those previously described for MEnk and noradrenaline (Chahl, 1983;1985). The lack of response to washout of somatostatin, 5 M, is shown in Figure 2.…”
Section: Effects Of Washoutsupporting
confidence: 73%
See 2 more Smart Citations
“…The washout contracture to adenosine, 5,uM, was abolished in seven preparations (from seven animals) by addition of the SP antagonist, spantide, 1O#UM, 30s before washout of the bath (Figure 1). Thus adenosine produced similar actions on the ileum to those previously described for MEnk and noradrenaline (Chahl, 1983;1985). The lack of response to washout of somatostatin, 5 M, is shown in Figure 2.…”
Section: Effects Of Washoutsupporting
confidence: 73%
“…Lack of effect of ocreotide on naloxone-precipitated MEnk withdrawal is shown in Figure 4. In three preparations somatostatin at a concentration of 5OpuM, did not inhibit the naloxone-precipitated MEnk withdrawal response, but in another three preparations, baclofen, (Chahl, 1986), and phentolamine precipitated withdrawal following 2 min contact with clonidine (Chahl, 1985). In the present experiments concentrations of naloxone (1pM) which precipitated withdrawal from pureceptor agonists (Chahl, 1986), did not produce a withdrawal contracture from the K-agonist, U-50,488H.…”
Section: Effects Of Agonists On the Opioid Withdrawal Responsecontrasting
confidence: 47%
See 1 more Smart Citation
“…Barrios et al (1993) reported that yohimbine precipitated withdrawal signs, such as jerks, head-shakes, defaecation, and weight loss in clonidinetreated mice. The clonidine withdrawal phenomenon is also demonstrated in isolated organs (Chahl 1985;Barrios et al 1993). These analogies suggest that similar mechanisms exist between the developments of dependence in the a 2 -adrenoceptor and opioid systems (Duggan et al 1994).…”
Section: Discussionmentioning
confidence: 89%
“…The propulsion can be delayed by clonidine and loperamide, an adrenergic ␣ 2 -receptor ag-onist and an -opioid receptor agonist, respectively [6] . It is well known that clonidine relaxes isolated intestine [7,8] and loperamide causes compulsive contractions in the gastrointestinal tract [9] . However, the clonidine-and loperamide-induced delay in the models of colonic propulsion has not been fully characterized.…”
Section: Introductionmentioning
confidence: 99%